2017
DOI: 10.4054/demres.2017.37.27
|View full text |Cite
|
Sign up to set email alerts
|

Economic crisis promotes fertility decline in poor areas: Evidence from Colombia

Abstract: BACKGROUNDThe effects of an economic recession extend beyond financial spheres and spill over into present and future family decisions via income restrictions and expectations. Hardly any research on the effects of economic recession on fertility outcomes has taken place in developing countries. OBJECTIVEThis study seeks to explain the effects of economic cycles on fertility outcomes in poor areas. METHODSThis paper analyzes fertility trends from the third largest economy in Latin AmericaColombia -from 1998 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…It is concluded that the Economic crisis has a bad impact on birth rates, and it can decline the birth rates especially at the time of crises. This result is in line with the results of (Davalos & Morales, 2017) examined the impacts of economic crises on birth rates. They had analyzed the data in Latin America-Colombia from 1998 to 2013.…”
Section: Literature Reviewsupporting
confidence: 91%
“…It is concluded that the Economic crisis has a bad impact on birth rates, and it can decline the birth rates especially at the time of crises. This result is in line with the results of (Davalos & Morales, 2017) examined the impacts of economic crises on birth rates. They had analyzed the data in Latin America-Colombia from 1998 to 2013.…”
Section: Literature Reviewsupporting
confidence: 91%
“…People with better personal economic conditions expected more children. Also, in countries and regions with high economic status, the fertility rate of local women was relatively higher ( 59 ). Therefore, it supported the result that the increase in family income could promote reproductive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…China apart, any government that introduces policies that increase the cost of having children and/or the proportion of women in the workforce, has the potential to contribute to a decline in TFR ( 27 ). The overall state of the economy is inevitably a major contributor to declining TFR as exemplified by the negative impact of economic recessions that look place in Spain in 2008 ( 28 ) and between 1998 and 2013 in the poorer areas of Columbia ( 29 ). Conversely, there are many examples of pronatalist policies that can have a positive impact on fertility including: baby bonuses in the form of cash transfers and tax incentives ( 30 ), Scandinavian-style parental leave schemes that provide parents with the opportunity to care for their child without suffering career disadvantage ( 31 ), provision of adequate childcare facilities ( 32 ) and the supply of affordable housing ( 33 , 34 ).…”
Section: Role Of Governmental Policies and Contraceptionmentioning
confidence: 99%